Mycobacterium avium subsp. paratuberculosis and food safety - Aydemir, Mehmet Emin; Arslan, Ali (Burdur Mehmet Akif Ersoy Üniversitesi, 2021)
Mycobacterium avium subsp. paratuberculosis (MAP) is the cause of Paratuberculosis (Johne’s disease) disease, Which observed in domestic ruminants an infectious disease characterized by chronic gastroenteritis, diarrhea and slimming. MAP is also reported to play a role in the etiology of Crohn’s disease (CD) in humans. For this reason, MAP is also important for public health. Since it is more resistant to pasteurization than other bacteria, it can be transmitted to people from contaminated milk and dairy products. In addition, contaminated by the feces of infected animals can be source of contamination meat, meat products, milk, dairy products and water. MAP is important in terms of food safety, as the probability of contamination with food from infected animals is very high. For this reason, detailed researches are needed to be done about the presence in foods and prevention of food contamination.

Mycobacterium avium subsp. paratuberculosis (MAP) evcil ruminantlarda görülen kronik gastroenteritis, ishal ve zayıflama ile karakterize enfeksiyöz bir hastalık olan Paratüberküloz (Johne’s hastalığı) hastalığının etkenidir. MAP ayrıca insanlarda görülen Crohn hastalığı (CH) etiyolojisinde de rol oynadığı bildirilmektedir. Bu nedenle MAP halk sağlığı açısından da önem arz etmektedir. Pastörizasyon işlemine diğer bakterilerden daha dayanıklı olduğundan kontamine süt ve süt ürünlerinden insanlara bulaşabilmektedir. Ayrıca hastalığı taşıyan hayvanların dışkısının bulaştığı et, et ürünleri, süt, süt ürünleri ve su bulaşma kaynağı olabilmektedir. MAP’ın enfekte hayvanlardan elde edilen besinlerle bulaşma olasılığının oldukça yüksek olması nedeniyle, gıda güvenliği açısından önem arz etmektedir. Bundan dolayı besinlerdeki varlığı ve besinlere bulaşmasının engellenmesi konusunda detaylı araştırmaların yapılmasına ihtiyaç duyulmaktadır.
Mycobacterium avium subsp. paratuberculosis ve gıda güvenliği
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi